Suicide with Hara-Kiri Like Method: A Case Report - Seydaoğulları Baltacı, Ayşe; Zeybek, Volkan; Tekin, Özgür; Acar, Kemalettin (The Bulletin of Legal Medicine, 2020)
Suicide is defined as “a person’s giving an end to his own life due to emotional, psychological, or social effects”. Many factors such as cultural structure, ethnic group, age, gender and accessibility are effective in the choice of suicide method. The most common suicide method is hanging, followed by firearms, jumping from heights and chemical intake. While the suicide with the sharp intruments constitutes %2 of all suicides, the incidence of suicide with the sharp intruments which is similar to Harakiri is % 0.2. What makes our case valuable is that the person belongs to the Turkish race and has chosen a suicide method as harakiri that is special to the Japanese race. A 56-year-old man diagnosed with psychotic disorder died of peritoneal, small intestine and mesenteric injuries due to abdominal and chest penetrating stab wounds and hypovolemic shock due to bleeding.